A new hybrid electrochemical-mechanical process (PEMEC) for polishing complex and rough parts. Issue 1 (2022) - Rech, J.; Krzak, D.; Roy, F.; Salvatore, F.; Gidon, A.; Guérin, S.
Abstract: A new polishing process for metallic parts has been developed by simultaneously coupling drag finishing and electrochemical polishing. This new hybrid process, called PEMEC, enables an improvement in the surface roughness within some minutes, and at the same time, preserves the shape of the edges. This hybrid process is based on a synergistic effect between abrasive and chemical mechanisms. It has confirmed its suitability to be applied on complex and rough surfaces produced by additive manufacturing SLM parts.